Interpersonal Communication and Work Motivation on the Performance of Civil Servants in Banyuasin Regency - Hadiwijaya, Hendra; Sulastri, Sulastri; Hanafi, Agustina; Widiyanti, Marlina (Universitas Nusantara PGRI Kediri, 2023)
Research aim : The purpose of this study is to prove the influence of interpersonal communication and work motivation on the performance of civil servants in Banyuasin Regency. Design/Method/Approach : The sample of this study were 197 Civil Servants with echelon III structural positions. The method of determining the sample used the saturated sample method (census). The data analysis technique in this study is using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique. Research Finding : The results of the study show that interpersonal communication and motivation have a positive effect on employee performance. This study also proves that the work motivation variable has a greater influence than the interpersonal communication variable on employee performance. Theoretical contribution/Originality : - Practitionel/Policy implication : - Research limitation : This research has implications for policies for performance appraisal related to interpersonal communication and work motivation.